1998
DOI: 10.1128/aac.42.3.666
|View full text |Cite
|
Sign up to set email alerts
|

Anti- Pneumocystis Activities of Aromatic Diamidoxime Prodrugs

Abstract: Aromatic dicationic compounds, such as pentamidine, have potent antimicrobial activities. Clinical use of these compounds has been restricted, however, by their toxicity and limited oral activity. A novel approach, using amidoxime derivatives as prodrugs, has recently been proposed to overcome these limitations. Although results were presented for amidoxime derivatives of only one diamidine, pentamidine, the authors in the original proposal claimed that amidoxime derivatives would work as effective prodrugs fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 39 publications
2
53
0
3
Order By: Relevance
“…administration, several diamidinocarbazoles were very effective against P. carinii pneumonia in an animal model. The dicationic carbazoles were inactive when given orally; however, they were considered good candidates for amidoxime pro-drugs [44,106,108]. Unexpectedly, as can be noted from Tab.…”
Section: Pro-drugs Of Carbazoles and Related Analogsmentioning
confidence: 95%
See 4 more Smart Citations
“…administration, several diamidinocarbazoles were very effective against P. carinii pneumonia in an animal model. The dicationic carbazoles were inactive when given orally; however, they were considered good candidates for amidoxime pro-drugs [44,106,108]. Unexpectedly, as can be noted from Tab.…”
Section: Pro-drugs Of Carbazoles and Related Analogsmentioning
confidence: 95%
“…The in vivo conversion of pentamidine dioxime to pentamidine has been noted [107]. However, on oral administration of pentamidine dioxime in the immunosuppressed rat model for PCP it was only moderately effective [106]. We have reported that the bisamidoxime and bis-O-methylamidoxime of furamidine (17) were quite effective anti-PCP agents in the rat model on both oral and intravenous administration (see Tab. 16.13) [108].…”
Section: Pro-drug Approaches For Furamidinementioning
confidence: 97%
See 3 more Smart Citations